(3eHOC YOe GdJONd hGJaGbjGJ JMQjQ GdJLGQI GdYGdejIs - (3jGSQ(B, (3GdMhjTs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2005)
(3GdbGfhf GdOhdj GdJLGQj hYdGbJg HGdbGfhf GdOhdj GdYGe(B- (3JWhjQ bhGYO GdbGfhf GdOhdj(B- (3eDSSGJ GdbGfhf GdOhdj GdJLGQj aj VhA GdJfXje GdOhdj(B- (3GdWHjYI GdbGfhfjI deHOC YOe GdJONd(B- (3GdENJUGU GdOGNdj cbjO Ydi GdJONd aj Xd GJaGbjGJ JMQjQ GdJLGQI GdYGdejIs
(3GdeQGLY U(B.795s
Keywords: (3GdEJaGbjGJ GdOhdjI(B- (3GdEJaGbjI GdYGeI ddJLGQI hGdJYQaI GdLeQcjI (B(1947)s; (3GdJLGQI GdNGQLjI(B- (3eYGgOGJs; (3GdbGfhf GdOhdj GdJLGQjs